2012
DOI: 10.1021/jp212326x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Interactions between DNA Oligomers and Graphite Surface Using Single Molecule Force Spectroscopy

Abstract: In single molecule force spectroscopy experiments, force probes chemically modified with synthetic, single-stranded DNA oligomers produced characteristic steady-state forces connected by abrupt steps between plateaus, as the probes moved away from a graphite substrate. The force plateaus represent peeling of a small number of polymer molecules from the flat surface. The final force jump in the retraction region of the force–distance curves can be attributed to a single DNA molecule detaching from the graphite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(92 citation statements)
references
References 54 publications
3
89
0
Order By: Relevance
“…Instead, the force plateaus can be interpreted as forced desorption or peeling of an extended length of the T4P from the underlying surface ( Fig. 1 a2), as observed using AFM for other semi-flexible polymer chains (33)(34)(35)(36). If the major pilin subunit mediates adherence, the adhesive force between the T4P and the surface should be constant along the length of the pilus, and the peeling force should remain constant over an extended range of tip-sample separations, producing a force plateau in the AFM force-separation curve (Fig.…”
Section: Afm Force Plateausmentioning
confidence: 90%
See 1 more Smart Citation
“…Instead, the force plateaus can be interpreted as forced desorption or peeling of an extended length of the T4P from the underlying surface ( Fig. 1 a2), as observed using AFM for other semi-flexible polymer chains (33)(34)(35)(36). If the major pilin subunit mediates adherence, the adhesive force between the T4P and the surface should be constant along the length of the pilus, and the peeling force should remain constant over an extended range of tip-sample separations, producing a force plateau in the AFM force-separation curve (Fig.…”
Section: Afm Force Plateausmentioning
confidence: 90%
“…We can understand the relationship between the peeling force f and the adhesion energy per unit length ε through the use of an equilibrium statistical model for the peeling of a freely-jointed-chain (FJC, Kuhn length a ¼ 2L p for the relaxed T4P) that is allowed to slide freely on a flat surface (35). A detailed analysis of this model is presented in the Supporting Material.…”
Section: Plateau Forces and Distribution Of Plateau Lengths For Diffementioning
confidence: 99%
“…For the statistical analysis, all data were expressed as means ± standard deviation (SD) for n>80 (n represents the number of data being analyzed). 26,27 When Hg 2+ is added into the system, a more rigid hairpin-shaped duplex DNA structure will form through formation of T-Hg 2+ -T complexes and folding of the aptamer. The strategy for Hg 2+ detection by our SMFS-based aptasensor is illustrated in Fig.…”
Section: Statistic Analysis Of Force Datamentioning
confidence: 99%
“…21 They reported that stacking interactions were favored in water and hydrogen bonded complexes in nonpolar solvents like carbon tetrachloride. Manohar et al 26 and Iliafar et al 27 conducted measurements of the binding strength of DNA homopolymers by atomic force microscopy-based single molecule force spectroscopy. 22 They also observed that hydrogen bonding interactions were mainly stabilized by electrostatic contribution to the free energies while stacking interactions were mainly stabilized by van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%